2011
DOI: 10.1017/jfm.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Corner effect and separation in transonic channel flows

Abstract: An investigation into parameters affecting separation in normal shock wave/boundary layer interactions (SBLIs) has been conducted. It has been shown that the effective aspect ratio of an experimental facility (defined as δ * /tunnel width) is a critical factor in determining when shock-induced separation will occur. Experiments examining M ∞ = 1.4 and 1.5 normal shock waves in a wind tunnel with a small rectangular cross-section have been performed and show that a link exists between the extent of shock-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 13 publications
4
64
2
Order By: Relevance
“…Furthermore, as mentioned in § 1.3, it is widely known that the inclusion of sidewalls can have large three-dimensional effects on the resulting flow (Bruce et al 2011;Burton & Babinsky 2012;Babinsky et al 2013;Benek et al 2013;Galbraith et al 2013;Wang et al 2015). We content that so-called three-dimensional effects, such as pressure disturbances generated by viscous flow phenomena in the Babinsky et al (2013), may also contribute to the 'non-canonical' development of the separation bubble (and hence separation shock) at the tunnel centreline.…”
Section: Free Interaction Theorymentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, as mentioned in § 1.3, it is widely known that the inclusion of sidewalls can have large three-dimensional effects on the resulting flow (Bruce et al 2011;Burton & Babinsky 2012;Babinsky et al 2013;Benek et al 2013;Galbraith et al 2013;Wang et al 2015). We content that so-called three-dimensional effects, such as pressure disturbances generated by viscous flow phenomena in the Babinsky et al (2013), may also contribute to the 'non-canonical' development of the separation bubble (and hence separation shock) at the tunnel centreline.…”
Section: Free Interaction Theorymentioning
confidence: 84%
“…Matheis & Hickel (2015) investigated transition in SWBLI numerically, but to the best of the authors' knowledge there exists no such experimental study on the topic. Furthermore, Matheis & Hickel (2015) chose not to include the effect of sidewalls; however, it is widely known that the inclusion of sidewalls can have a large effect on the resulting flow (Bruce et al 2011;Burton & Babinsky 2012;Babinsky et al 2013;Benek, Suchyta III & Babinsky 2013;Galbraith et al 2013;Wang et al 2015). An experimental study would naturally include sidewall effects.…”
Section: Motivationmentioning
confidence: 99%
“…The interaction between two separated flow regions is the focus of the present work; previously Bruce et al (2011) and Burton & Babinsky (2012) have shown that reducing the size of one region can increase the size of the other. They explain that when an adverse pressure gradient is applied (by a complex 3-D shock wave structure, for example) the pressure gradient will be distributed in space.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…They discussed how waves emanating from the corner act to smear the adverse pressure gradient imposed upon other parts of the flow. Using the same wind tunnel, Bruce et al (2011) varied several factors that affect the onset of separation and the sizes of separation regions. They found that modifying the corner region significantly affects the separation on the bottom wall, and they explain that altering the corner flow changed the shape of the shock wave.…”
Section: Previous Related Sbli Researchmentioning
confidence: 99%
“…The side walls are likely to; (i) cause flow separation near the leading edge of the aerofoil (in the vicinity of the side walls), and (ii) promote confinement effects. But side wall effects are to be small as the thinner aerofoil boundary-layer usually dictates the extent of the side-wall interaction [2].…”
Section: Simplified Experiments Flow Fieldmentioning
confidence: 99%